Answer:
(7, 0 )
Step-by-step explanation:
Given the 2 equations
y = - 2x + 14 → (1)
y = 2x - 14 → (2)
Since both equations express y in terms of x we can equate them
2x - 14 = - 2x + 14 ( add 2x to both sides )
4x - 14 = 14 ( add 14 to both sides )
4x = 28 ( divide both sides by 2 )
x = 7
Substitute x = 7 into (2) for corresponding value of y
y = (2 × 7) - 14 = 14 - 14 = 0
Solution is (7, 0 )
E and G are congruent because they are vertical.
Hey there! :)
Answer:
b = -11.
Step-by-step explanation:
Create an equation in slope-intercept form to solve for the intercept:
y = mx + b
Plug in the slope and point values:
4 = -3(-5) + b
Simplify:
4 = 15 + b
Solve for b:
-11 = b
b represents the y-intercept, therefore:
y-intercept = -11
Answer:
A
Step-by-step explanation:
Given
- 2 +
= 6 ( isolate the radical by adding 2 to both sides )
= 8 ( square both sides )
3x - 2 = 8² = 64 ( add 2 to both sides )
3x = 66 ( divide both sides by 3 )
x = 22 → A